Enhancing Liquidity in the Indian Commodity Derivatives Markets: Linking Agriculture Trade to Commodity Derivative Markets - T. K. Soni; A. Singh (Финансы: теория и практика, 2024)
Integrating participants in the agricultural value chain, including farmers, traders, aggregators, processors, etc., into commodity derivative markets can become a win-win option for all stakeholders in the commodity ecosystem. Participants may gain an advantage related to price setting and risk management; on the other hand, exchanges may benefit from increased liquidity. In this same context, the article presents a conceptual scheme for attracting value chain agents in agriculture to Indian commodity exchanges. Within the framework of this concept, special attention is given to raising the awareness of producers, processors, and consumers of agricultural products about the benefits of commodity derivative markets. The issue of incentivizing hedgers and participants, who should have real exposure to commodities, is also being considered to increase their participation in the operations of Indian exchanges. Moreover, it is recommended to encourage indirect participation through option traders, investment banks, or other specialized agencies. In the long term, other strategies can also be considered, including state participation in commodity derivatives markets and allowing fractional contracts on commodity derivatives to increase liquidity in Indian commodity derivatives markets.